Increasing Students' Active Participation in PPKN Subject Through Portfolio-Based Learning Model in Class VIII-G at SMPN 5 Mataram - Adawiah, Radiatul; Zubair, Muh.; Hudori, Ahmad; Sawaludin, Sawaludin (UNDIKMA, 2024)
This study aims to increase students' active participation in the Pancasila and Citizenship Education (PPKn) subject through the application of a portfolio-based learning model for class VIII-G at SMP Negeri 5 Mataram. This study uses research. This study uses Classroom Action Research (CAR) with data collection techniques through interviews, observations, tests, and documentation. The stages in this study are planning, action, observation and reflection. The subjects of the classroom action research were students of class VIII-G of SMP 5 Mataram. The data analysis techniques used were qualitative and quantitative. In cycle I, the percentage of active student participation reached 57% of the total number of students present, but after improvements were made in cycle II, the percentage of active student participation increased to 87% and in cycle III, the percentage of active student participation increased to 94%. Therefore, the portfolio-based learning model can increase the active participation of students where the percentage of success in this classroom action research has exceeded the indicator of the success of active student participation that has been determined from the beginning, a minimum of 75% success of the action. Based on the results of the data for each cycle, it shows that the use of a portfolio-based learning model in learning Pancasila and Citizenship Education (PPKn) in class VIII-G at SMP Negeri 5 Mataram can increase the active participation of students